Twitter and cartoons to problematize socio-political aspects in today's education (Revista Electrónica Diálogos Educativos. REDE, 2017)
Education in Venezuela is facing a serious crisis in many aspects, since it not only faces a process of changes and transformations in curricular redesign but also is influenced by social, political, economic conflicts, among others. On the other hand, the political polarization so marked that is presented in the country leads to generate distortions in the way of seeing the current social phenomena. That is why this article aims to promote the use of twitter and cartoons as ways to problematize socio-politicalÂ aspects in today's education. These two tools are presented to highlight the reflection of Venezuelan reality and proposes the generation of spaces for serious educational debates that promote discussions in order to visualize an education less distant from day to day reality and, on the contrary, draws attention to being part of a reality. Educational centers are not only spaces for discussing aspects of specific disciplines. We must know how to recognize virtues and weaknesses in each of our areas of habitability to make a much more harmonious coexistence, and to promote criticality in students through these technological tools.